Faktor-faktor yang Berhubungan dengan Perilaku Karyawan dalam Membuang Limbah Medis di RSUD Undata Palu Sulawesi Tengah - , Hilbert Tanonggi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Problem of environment is closely correlated to world of health. To achieve healthy public condition, we need a good environment. In this case, hospital as a health instrument must consider the correlation. Hospital is a health medium which is correlated to various diseases (inand- outpatients), and gives medical service (physicians, nurses) and others such as group of patients, group of service providers, group of visitors and group of surrounding environment. Each hospital produces waste, including medical waste which must be managed properly. In 2000, results of WHOâs research conducted in 22 developing countries indicated that proportion of healthcare facilities which did not use appropriate waste disposal method was approximately ranged from 18% to 64%. Objectives: To find factors correlating to employeesâ behavior in disposing medical waste in Undata Hospital of Palu. Method: This research used observation with cross-sectional design. Respondents of this research were 840 employees of the Undata Hospital of Palu and 152 subjects, employees working in unit of medical waste producer. Whereas statistical test of bivariate analysis was chi-square and multivariate analysis was logistic regression, with significance degree (Î±)=0.05. Results: The results of bivariate analysis indicated that there were four correlating variables, namely, education, attitude, work period and policy of hospital. The results of multivariate analysis indicated that there were three most significant variables, namely, education, p=0.0062, OR = 4.10101